2008
DOI: 10.1111/j.1467-7652.2008.00375.x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of stable ‘low phytic acid’ transgenic rice through antisense repression of the 1dmyo‐inositol 3‐phosphate synthase gene (RINO1) using the 18‐kDa oleosin promoter

Abstract: Summary Phytic acid acts as the major storage form of phosphorus in plant seeds and is poorly digested by monogastric animals. The degradation of phytic acid in animal diets is necessary to overcome both environmental and nutritional issues. The enzyme 1d‐myo‐inositol 3‐phosphate [Ins(3)P1] synthase (EC 5.5.1.4) catalyses the first step of myo‐inositol biosynthesis and directs phytic acid biosynthesis in seeds. The rice Ins(3)P1 synthase gene (RINO1) is highly expressed in developing seed embryos and in the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 58 publications
0
74
0
Order By: Relevance
“…Ali et al (2013) also developed low-phytate rice with no apparent developmental defects by seed-specific silencing of IPK1. However, defects in seed weight, germination frequency, and seedling emergence were observed in several other trials, reflecting a role for InsP 6 in seed development (Bilyeu et al, 2008;Kuwano et al, 2009;Li et al, 2014). In this study, we have shown that expression of InsP 6 -sensitive Gle1 variants enhanced plant growth, seed yield, and seed performance of the phytate-deficient ipk1 mutant, suggesting a novel strategy for improving lpa plants.…”
Section: Discussionmentioning
confidence: 76%
“…Ali et al (2013) also developed low-phytate rice with no apparent developmental defects by seed-specific silencing of IPK1. However, defects in seed weight, germination frequency, and seedling emergence were observed in several other trials, reflecting a role for InsP 6 in seed development (Bilyeu et al, 2008;Kuwano et al, 2009;Li et al, 2014). In this study, we have shown that expression of InsP 6 -sensitive Gle1 variants enhanced plant growth, seed yield, and seed performance of the phytate-deficient ipk1 mutant, suggesting a novel strategy for improving lpa plants.…”
Section: Discussionmentioning
confidence: 76%
“…The generation of double or triple knockout mutants for the MIPS/IPS gene family should help determine the role of these genes in Arabidopsis InsP 6 metabolism. Alternatively, MIPS/IPS genes may be suppressed using anti-sense or RNAi-mediated gene silencing approaches which have been successfully employed in rice (Kuwano et al 2009) and soybean (Nunes et al 2006). Since T-DNA insertion mutants were obtained for only two of the four AtIMP genes, it is possible that the other genes have a role in seed InsP 6 levels.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have developed transgenic golden rice with reduced LOX activity by silencing endogenous lipoxygenase gene to reduce co-oxidation of carotenoids using RNAi technology which is very powerful tool for crop improvement (Saurabh et al 2014). The RNAi-mediated gene silencing of lox gene was driven by tissue-specific Oleosin-18 promoter instead of any constitutive promoter to avoid any undesirable and detrimental effects on the plant (Kuwano et al 2009;Ali et al 2013).…”
Section: Discussionmentioning
confidence: 99%